Hippocampal glucocorticoid receptor and microRNA gene expression and serum cortisol concentration in foxes selected for behavior toward humans - V. Yu. Ovchinnikov; E. V. Antonov; G. V. Vasilyev; S. G. Shihevich; D. V. Shepeleva; Yu. E. Herbeck (Вавиловский журнал генетики и селекции)
In many cases, stress reactivity is one of the important bases of aggressive behavior. It appears as if reduced stress reactivity underlies an abrupt decrease in aggression towards man in domesticated animals. However, the mechanisms of this reduction have yet to be resolved. In this work, we used an experimental domestication model, the silver fox selected for many years for the response to humans to study cortisol stress reactivity in tame and aggressive foxes in response to immobilization in human arms. Additionally, these behavioral fox groups were explored for one of the important mechanisms of glucocorticoid negative feedback, the expression of the glucocorticoid receptor gene (NR3C1) in a portion of the dorsal hippocampus. In recent years, attention has been paid to differences in miRNA expression patterns between animals with different behavior and stress reactivity, as well as to miRNA regulation under stress. The same applies to NR3C1 mRNA as well. That is why we performed a miRNA-seq analysis on a portion of the fox dorsal hippocampus. It has been demonstrated that immobilization in human arms leads to significantly higher stressinduced cortisol levels in aggressive than tame foxes. At the same time, no differences have been found between hippocampal NR3C1 gene expression and the pattern of miRNA expression. Thus, reduced stress reactivity in foxes during selection for the absence of aggressive responses and for the presence of emotionally positive responses to humans does not seem to be associated with important mechanisms of regulation such as alterations in hippocampal NR3C1 gene expression or microRNA-mediated silencing.